Peritoneal transport properties and dialysis dose affect growth and nutritional status in children on chronic peritoneal dialysis - Schaefer, Franz; Klaus, Günter; Mehls, Otto (Journal of the American Society of Nephrology, 1999)
Abstract. To evaluate a possible effect of peritoneal transport properties and dialysis dose on the physical development of children on chronic peritoneal dialysis, a cohort of 51 children was prospectively followed for 18 mo. Peritoneal transport characteristics were assessed by serial peritoneal equilibration tests (PET), dialysis efficacy by dialysate and residual renal clearance measurements, and growth and nutritional status by the longitudinal changes (Δ) of height SD score (SDS), body mass index (BMI) SDS, and serum albumin. Δ height SDS was negatively correlated with the creatinine equilibration rate observed in the initial PET (r = -0.31, P < 0.05). Multiple regression analysis confirmed the negative effect of the high transporter state (partial r2 = 0.07), and disclosed an additional positive effect of dialytic CCr (partial r2 = 0.11) and a weak negative effect of daily dialysate volume (partial r2 = 0.04) on Δ height SDS. Δ BMI SDS was strongly age-dependent (r = -0.48, P < 0.001); while relative body mass gradually increased below 4 yr of age, it remained stable in older children. Positive changes in BMI SDS were associated with rapid PET creatinine equilibration rates (univariate r = 0.35, P < 0.05) and/or large dialysate volumes (multivariate partial r2 = 0.11), suggesting a role of dialytic glucose uptake in the development of obesity. The change in serum albumin concentrations was positively correlated with dialysate volume (partial r2 = 0.14), and negatively affected by dialytic protein losses (partial r2 = 0.06). In conclusion, the peritoneal transporter state is a weak but significant determinant of growth and body mass gain in children on chronic peritoneal dialysis. Rapid small solute equilibration contributes to impaired growth but enhanced acquisition of body mass. Dialytic small solute clearance has a weak positive effect on statural growth independent of the transporter state, but does not affect body mass gain.
Gesehen am 14.01.2021